SAO extraction on patent discovery system development for Islamic finance and banking - Othman, Roslina; Noordin, Mohamad Fauzan; Gusmita, Ria Hari; Tengku Sembok, Tengku Mohd; Zulkifli, Zahidah (IEEE, 2016)
This paper presents our work on Subject-ActionObject (SAO) extraction as one component needed on patent discovery system development for Islamic Finance and Banking. There are some process have been done in order to conduct SAO extraction. They are covering retrieving patent and transforming patent into structured data. We used several patent database such as USPTO, MyIPO, WIPO, and EPO to collect patent. In patent searching, we used keywords that came from Islamic Finance and Banking phrase, book’s title that has content about Islamic Finance and Banking, and all concepts on Islamic Finance and Banking ontology. Result on SAO extraction will be utilized on the next component on the system i.e. analyzing patent trend using TRIZ evolution trend model.